Computers in Agriculture and Natural Resources, 23-25 July 2006, Orlando Florida
DOI: 10.13031/2013.21839
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Agricultural Technologies through Interactive Multimedia Compact Disc (IMCD): An Innovative Approach

Abstract: Farming community in India is normally endowed with fragmented land holdings, containing marginal and small sectors to the maximum, the affordability, accessibility and possibility to travel a long distance and to hunt the information is seldom possible. As the traditional agriculture is transforming into hi-tech agriculture, the need for updated information is also essential for agricultural production and productivity, eventually giving a lucrative yield and income to the farming community. Improved communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…In the research area, developed IEMM on GDFPS were handed over to the concerned department officials for public access.The findings of the study are in conformity with the results reported by Anandaraja (2002), Mooventhan (2006) and Vidya et al (2010).…”
supporting
confidence: 92%
“…In the research area, developed IEMM on GDFPS were handed over to the concerned department officials for public access.The findings of the study are in conformity with the results reported by Anandaraja (2002), Mooventhan (2006) and Vidya et al (2010).…”
supporting
confidence: 92%
“…Moreover, the highly significant 't' values once again confirm statistically, the considerable knowledge gain among the farmers due to the treatment. The findings of the study are in conformity with the results reported by Anandaraja (2002), Mooventhan (2006) and Vidya et al (2010).…”
supporting
confidence: 92%
“…Studies have reported a cost effective delivery of agricultural information through community television and radio services (Hassan et al, 2008); Kweku, 2006, cited in Munyua, Adera, & Jensen, 2008Parikh, 2009). CD and DVD usage for delivery of agricultural learning modules have proved to be viable dissemination media (Anandaraja et al, 2009;Pye et al, 2003, cited in Munyua, Adera, & Jensen, 2008Parikh, 2009;Sheriff, 2009). The use of these self learning modules has been found to reduce dependency on technical staff for acquiring new agricultural knowledge.…”
Section: Use Of Internet and Communication Technologies (Ict) In Agri...mentioning
confidence: 99%